Dampak E-Commerce Tiktok Shop Terhadap Perilaku Konsumtif Mahasiswa Kalbar Berdasarkan Perspektif Ekonomi Islam - Sabpira Ramatun; Aiyub Anshori; Anwari, Muhammad Khairul (Jurnal Ilmiah Ekonomi Islam, 2025)
In the increasingly developing digital era, e-commerce has become a significant phenomenon in the world of commerce. One e-commerce platform that is increasingly popular is TikTok Shop, which offers various products to users through shopping features integrated into the TikTok application. This phenomenon also has an impact on the consumption behavior of students, who are a group that is active in using the platform. This type of research uses a quantitative approach by analyzing numerical data using statistical methods. The data collection technique is by distributing questionnaires to respondents (students) via Google Form with a Likert scale assessment. Population and Sample The population of this research is all students in West Kalimantan Province and a sample of 132 respondents. Variables This research uses seven research variables where the exogenous variables are lifestyle motives (MGH), motivational motives (MM), advertising and promotion motives (MIP), entertainment motives (MH), information motives (MI), and trust motives (MK). Meanwhile, the endogenous variable is consumer behavior (PK). The analysis data used uses the Partial Least Squares – Structural Equation Modeling (PLS-SEM) model. Based on the research results, entertainment motives (MH), advertising and promotion motives (MIP), motivational motives (MM) significantly influence consumer behavior (PK), however lifestyle motives (MGH), information motives (MI), trust motives (MK) do not have a significant influence on consumptive behavior (PK) in the impact of Tiktok shop e-commerce.